The role of macrophages in rosacea: implications for targeted therapies - Liu, Yi; Zhou, Yin; Chu, Chenyu; Jiang, Xian (Frontiers in Immunology, 2023)
Introduction Rosacea, a widespread chronic skin condition, may be influenced by macrophages, key immune cells in the skin, although their exact role is not yet fully understood. This review delves into the function of macrophages, their potential contribution to rosacea pathogenesis, current treatments, and promising macrophage-targeted therapies. It concludes by identifying knowledge gaps and potential areas for future rosacea research. Method Leveraging systematic and narrative literature review techniques, we conducted a comprehensive search of databases such as PubMed, Embase, and Web of Science. Utilizing keywords like “rosacea” and “macrophages”, we targeted English articles from the last 5 years (2018-2023). We manually checked reference lists of relevant articles for additional studies. We included only articles emphasizing macrophages’ role in rosacea and/or the development of related therapies and published within the specified timeframe. Results The systematic search of electronic databases yielded a total of 4,263 articles. After applying the inclusion and exclusion criteria, 156 articles were selected for inclusion in this review. These articles included original research studies, review articles, and clinical trials that focused on the role of macrophages in rosacea and/or the development of macrophage-targeted therapies for the disease. The selected articles provided a comprehensive and up-to-date overview of the current state of research on macrophages in rosacea, including their function in the skin, the potential mechanisms through which they may contribute to rosacea pathogenesis, and the current treatments and therapies available for the disease. Additionally, the articles identified gaps in knowledge regarding the role of macrophages in rosacea and suggested potential areas for future research. Conclusion This literature review emphasizes the important role that macrophages, vital immune cells in the skin, may play in the pathogenesis of rosacea, a common chronic inflammatory skin disorder. The selected studies suggest potential mechanisms by which these cells might contribute to rosacea progression, although these mechanisms are not yet fully understood. The studies also spotlight current rosacea treatments and illuminate the promising potential of new macrophage-focused therapies. Despite these insights, significant gaps persist in our understanding of the precise role of macrophages in rosacea. Future research in this area could provide further insights into the pathogenesis of rosacea and contribute to the development of more effective, targeted therapeutic strategies.